Kefir – a fermented milk product beneficial for gastrointestinal health - Mitra, Sonanki; Ghosh, Bikash C (Indian Journal of Dairy Science, 2021)
Kefir is becoming increasingly popular as a result of new research into its health benefits. It is a fermented product which originated in the Caucasus Mountains of Russia. Kefir is produced by the action of bacteria and yeasts existing in symbiotic association in kefir grains. The composition of kefir varies according type of milk and the microbiological composition of culture types (kefir grainÂ or commercial starter culture). Kefirâ€™s distinctive flavour is attributed by lactic acid, ethanol, carbon dioxide and other flavouring agents, such as acetaldehyde and acetoin. The microorganisms in kefir produce vitamins, degrade protein and hydrolyse lactose making it a highly nutritious and digestible product. Kefir has a long history of health benefits in Eastern European countries. In this review, manufacturing technologies, physicochemical properties, microbiological composition, therapeutic activities (viz. antimicrobial, anti-carcinogenic, immunomodulatory, probiotic properties etc.) as well as other health benefits, like reducing cholesterol and improving lactose tolerance have been summarised.